Construction of approximations for a stationary solution of a system of singular ordinary differential equations - Romanyshyn, I. M.; Synyts’kyi, L. A. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We propose a procedure for the construction of successive approximations of a stationary solution of a system of nonlinear ordinary differential equations with a small parameter with the derivative. We present sufficient conditions for the convergence of constructed approximations to the required stationary solution.